2007
DOI: 10.1073/pnas.0707426104
|View full text |Cite
|
Sign up to set email alerts
|

Polylactosamine on glycoproteins influences basal levels of lymphocyte and macrophage activation

Abstract: ␤1,3-N-acetylglucosaminyltransferase 2 (␤3GnT2) is a polylactosamine synthase that synthesizes a backbone structure of carbohydrate structures onto glycoproteins. Here we generated ␤3GnT2-deficient (␤3GnT2 ؊/؊ ) mice and showed that polylactosamine on N-glycans was markedly reduced in their immunological tissues. In WT mice, polylactosamine was present on CD28 and CD19, both known immune costimulatory molecules. However, polylactosamine levels on these molecules were reduced in ␤3GnT2 ؊/؊ mice. ␤3GnT2 ؊/؊ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 45 publications
(37 reference statements)
5
97
0
1
Order By: Relevance
“…Immunoprecipitated materials were blotted with 5D4 or the 6B4 mouse monoclonal anti-phosphacan antibody. Lectin blot analysis for the materials was performed with LEL, which binds to polylactosamines (Togayachi et al 2007). The asterisk indicates the position of the immunoglobulin heavy chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoprecipitated materials were blotted with 5D4 or the 6B4 mouse monoclonal anti-phosphacan antibody. Lectin blot analysis for the materials was performed with LEL, which binds to polylactosamines (Togayachi et al 2007). The asterisk indicates the position of the immunoglobulin heavy chain.…”
Section: Discussionmentioning
confidence: 99%
“…5). The 6B4 mouse monoclonal antibody and LEL, a lectin that binds to polylactosamine (Togayachi et al 2007), recognized bands in 6B4 immunoprecipitate samples of all three genotypes (Fig. 5).…”
Section: Loss Of the 5d4 Epitope In Phosphacan Expressed In P1 Brainsmentioning
confidence: 99%
“…To investigate whether hematocytes manifest aberrant cell distribution or development in B3gnt5 −/− mice, we analyzed the expression of a series of CD antigens on the cell surface of peripheral blood and splenic cells using FCM. The antigens investigated were the same as those described in a previous study (19). No significant disturbance in the ratios of cell populations, such as T cells, B cells, monocytes, or granulocytes, was observed.…”
Section: Resultsmentioning
confidence: 99%
“…B3gnt2 (β3GnT2) mRNA is ubiquitously expressed in mouse tissues, and thus also in B cells, T cells, and other immune cells. The previous study demonstrated that B3gnt2 −/− B and T cells, which lack polylactosamine (PLN) on the N-glycans of their glycoproteins, showed hyperactivation following BCR or TCR/CD28 stimulation (19). Thus, PLN chains on glycoproteins have an important role in determining thresholds for in vitro immunocyte activation.…”
mentioning
confidence: 99%
“…The glycosylation of polylactosamine uses repeating Galβ1-4-glucosyl (Glc)-N-acetyl-(Ac)-β1-3 disaccharide units that are preferentially joined to β1-6GlcNAc-linked antennae that are connected to the trimannosyl core of the complex-type N-linked oligosaccharides (8). It has been reported that highly metastatic colon cancer cells synthesize more N-glycans that contain polylactosamine than cells with low metastasis (9).…”
Section: (Acetylamino)-2-deoxy-α-d-galactopyranosyl]-l-sementioning
confidence: 99%